Educação, valores morais e a visibilidade social no desenvolvimento do sujeito - Vera Lucia Trevisan de Souza; Vera Maria Nigro de Souza Placco (Arquivos Brasileiros de Psicologia, 2014)
This article examines the values present in school in its process of subject constitution. It is part of a research in which the investigation was made about respect in school in its moral qualifications. It has been found in the investigation that non-moral values are present in the interactions between children and adults frequently, favouring its construction and maintainance. This kind of values is a most important aspect in the constitution of the self.